Late Cenozoic transpression at the plate boundary: Kinematics of the eastern segment of the Dauki Fault Zone (Bangladesh) and tectonic evolution of the petroliferous NE Bengal Basin. (September 2021) - Hossain, Md. Sakawat; Khan, Md. Sharif Hossain; Abdullah, Rashed; Mukherjee, Soumyajit
Abstract: The Sylhet Trough in the Bengal Basin (Bangladesh) hosts a number of gas fields. The evolution of the trough is closely associated presumably with the growth and the tectonics of the Dauki Fault Zone (DFZ). Hence understanding the transpression tectonics of the NE Bengal Basin is crucial in petroleum geoscience. The eastern segment of the DFZ in the NE Bengal Basin transpressed dextrally and activated since the latest Miocene up to the earliest Pliocene due to compression along the north, east and southeast. The structural and the tectonic elements of the area are assessed from geomorphic features and deformation structures. Nature of faults and comparison of fault-slip stress field with modern geodetic measurement allow establishing geometric and kinematic relationship between different tectonic elements with the DFZ. Bedding attitude measurements from the study area indicate sub-horizontal east–west-trending antiform fold axis gently plunging towards west confirming the existence of a large-scale monocline. Out of the two interpreted compression directions N–S and E-W, the former explains the orientation of the monocline while the later may cause the dextral transpression in combination with the former compression direction. Fault kinematics and incremental strain axes indicate a bulk north-trending subhorizontal shortening and vertical thickening of the fold and faults approximately perpendicular to the east-west oriented DFZ. The timing of the compressional deformation and fault activation in the study area is inconclusive. Paleostress analyses results match with the present day stress regime and this implies that all the deformations are genetically linked with the DFZ. Highlights: Tectonics of Dauki Fault Zone studied. Paleostress analyses results match with present day stress regime. The work will be important in petroleum geosciences of a part of the Surma basin.